Barriers and facilitators to HIV and sexually transmitted infections testing for gay, bisexual, and other transgender men who have sex with men. Issue 8 (3rd August 2017) - Scheim, Ayden I.; Travers, Robb
ABSTRACT: Transgender men who have sex with men (trans MSM) may be at elevated risk for HIV and other sexually transmitted infections (STI), and therefore require access to HIV and STI testing services. However, trans people often face stigma, discrimination, and gaps in provider competence when attempting to access health care and may therefore postpone, avoid, or be refused care. In this context, quantitative data have indicated low access to, and uptake of, HIV testing among trans MSM. The present manuscript aimed to identify trans MSM's perspectives on barriers and facilitators to HIV and STI testing. As part of a community-based research project investigating HIV risk and resilience among trans MSM, 40 trans MSM aged 18 and above and living in Ontario, Canada participated in one-on-one qualitative interviews in 2013. Participants described a number of barriers to HIV and other STI testing. These included both trans-specific and general difficulties in accessing sexual health services, lack of trans health knowledge among testing providers, limited clinical capacity to meet STI testing needs, and a perceived gap between trans-inclusive policies and their implementation in practice. Two major facilitators were identified: access to trusted and flexible testing providers, and integration of testing with ongoing monitoring for hormone therapy. Based on these findings, we provide recommendations for enhancing access to HIV and STI testing for this key population.